1997
DOI: 10.1095/biolreprod57.5.1211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intrafollicular Steroid Hormones, Inhibin, and Follistatin in Women with and without Polycystic Ovarian Syndrome Following Gonadotropin Hyperstimulation1

Abstract: The etiology of polycystic ovary syndrome (PCOS) is unexplained. Since no major deficiencies are reported in serum FSH or inhibin, we hypothesized that abnormal levels of a paracrine modulator of FSH action within the ovary may be associated with the arrest of follicular growth seen in the PCOS ovary. Follicular fluid aspirates were collected from women with (n = 7) or without (n = 17) PCOS during oocyte retrieval for in vitro fertilization. Aspirates were assayed for total inhibin, inhibin A (InhA), inhibin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…In the present study, levels of inhibin-B in group II and III reached only approximately 60% of that observed in the control group, suggesting that androgens, which were artificially kept high by the use of aromatase inhibitor, are the cause of the attenuated granulosa cell production of inhibin-B. The inhibin-B content of preovulatory FF from women with polycystic ovary syndrome (PCOS) and healthy women who underwent ovarian stimulation with exogenous gonadotropin has been reported to be similar (11). This is in contrast to observations on FF from women with PCOS who did not receive ovarian stimulation.…”
Section: Discussionmentioning
confidence: 50%
“…In the present study, levels of inhibin-B in group II and III reached only approximately 60% of that observed in the control group, suggesting that androgens, which were artificially kept high by the use of aromatase inhibitor, are the cause of the attenuated granulosa cell production of inhibin-B. The inhibin-B content of preovulatory FF from women with polycystic ovary syndrome (PCOS) and healthy women who underwent ovarian stimulation with exogenous gonadotropin has been reported to be similar (11). This is in contrast to observations on FF from women with PCOS who did not receive ovarian stimulation.…”
Section: Discussionmentioning
confidence: 50%
“…Elevated inhibin B levels are closely related to an elevated risk of developing PCOS (Magoffin and Jakimiuk, 1997; Anderson et al ., 1998; Lockwood et al ., 1998). In addition, studies have shown that inhibin A and B levels are significantly reduced in the FF of women with PCOS, when compared with FF levels of size-matched follicles from NOW (Lambert-Meserlian et al ., 1997; Welt et al ., 2005). Therefore, activin, FS and inhibins bring about intra-ovarian actions through paracrine/autocrine systems, playing an important role in maintaining folliculogenesis; their imbalance may be directly correlated to the pathogenesis of PCOS, consequently impairing oocyte maturity, embryo quality and pregnancy outcome.…”
Section: Intra-ovarian Factorsmentioning
confidence: 99%
“…Inhibin A and B concentrations also are decreased in some, but not all, small PCOS follicles, despite normal amounts of activin and follistatin unbound to activin (150, 157). Although exogenous FSH stimulates the growth of PCOS follicles, intrafollicular inhibin A levels in PCOS patients receiving gonadotropin-releasing hormone (GnRH) analog/gonadotropin therapy for IVF remain reduced (158). On the other hand, serum inhibin B levels arising from the multiple small follicles are elevated in PCOS patients (159) and are suppressed by exogenous hCG and endogenous insulin (160), linking defective inhibin biosynthesis with follicular arrest, likely by reducing FSH levels (151).…”
Section: Antral Follicle Developmentmentioning
confidence: 99%